From 763c9022ca375271ebffd8e26fe041cd2c639686 Mon Sep 17 00:00:00 2001 From: arc Date: Sun, 16 Feb 2025 18:52:21 -0700 Subject: [PATCH] vault backup: 2025-02-16 18:52:21 --- .obsidian/plugins/obsidian-git/data.json | 27 +++++++++++++++++++ .../math/MATH1210 (calc 1)/Derivatives.md | 20 +++++++++----- 2 files changed, 41 insertions(+), 6 deletions(-) diff --git a/.obsidian/plugins/obsidian-git/data.json b/.obsidian/plugins/obsidian-git/data.json index e69de29..bef4c6e 100644 --- a/.obsidian/plugins/obsidian-git/data.json +++ b/.obsidian/plugins/obsidian-git/data.json @@ -0,0 +1,27 @@ +{ + "commitMessage": "vault backup: {{date}}", + "autoCommitMessage": "vault backup: {{date}}", + "commitDateFormat": "YYYY-MM-DD HH:mm:ss", + "autoSaveInterval": 5, + "autoPushInterval": 0, + "autoPullInterval": 5, + "autoPullOnBoot": true, + "disablePush": false, + "pullBeforePush": true, + "disablePopups": false, + "listChangedFilesInMessageBody": false, + "showStatusBar": true, + "updateSubmodules": false, + "syncMethod": "merge", + "customMessageOnAutoBackup": false, + "autoBackupAfterFileChange": false, + "treeStructure": false, + "refreshSourceControl": true, + "basePath": "", + "differentIntervalCommitAndPush": false, + "changedFilesInStatusBar": false, + "showedMobileNotice": true, + "refreshSourceControlTimer": 7000, + "showBranchStatusBar": true, + "setLastSaveToLastCommit": false +} \ No newline at end of file diff --git a/education/math/MATH1210 (calc 1)/Derivatives.md b/education/math/MATH1210 (calc 1)/Derivatives.md index cd116f7..90fa3d5 100644 --- a/education/math/MATH1210 (calc 1)/Derivatives.md +++ b/education/math/MATH1210 (calc 1)/Derivatives.md @@ -121,7 +121,7 @@ $$ \dfrac{d}{dx} (x^2 + 3)^4 = 4(x^2 + 3)^3 * (2x)$$ > Apply the chain rule to $x^4$ If we treat the above as a function along the lines of $f(x) = (x)^4$, and $g(x) = x$, then the chain rule can be used like so: -$$ 4(x)^3 * x $$ +$$ 4(x)^3 * (1) $$ # Trig Functions $$ \lim_{x \to 0} \dfrac{\sin x}{x} = 1 $$ $$ \lim_{x \to 0} \dfrac{\cos x - 1}{x} = 0 $$ @@ -150,12 +150,20 @@ $$ \dfrac{d}{dx} \cot x = -\csc^2 x $$ - $\dfrac{d}{dx} x = \dfrac{dx}{dx} = 1$ : The derivative of $x$ with respect to $x$ is one - $\dfrac{d}{dx} y = \dfrac{dy}{dx} = y'$ - Given the equation $y = x^2$, $\dfrac{d}{dx} y = \dfrac{dy}{dx} = 2x$. + +Given these facts: +1. Let $y$ be some function of $x$ +2. $\dfrac{d}{dx} x = 1$ +3. $\dfrac{d}{dx} y = \dfrac{dy}{dx}$\ +What's the derivative of $y^2$? +$\dfrac{d}{dx} y^2 = 2(y)^1 *\dfrac{dy}{dx}$ + # Examples > Differentiate $f(x) = 4\sqrt[3]{x} - \dfrac{1}{x^6}$ -2. $f(x) = 4\sqrt[3]{x} = \dfrac{1}{x^6}$ -3. $= 4x^\frac{1}{3} - x^{-6}$ -4. $f'(x) = \dfrac{1}{3} * 4x^{-\frac{2}{3}} -(-6)(x^{-6-1})$ -5. $= 4x^{-2-\frac{2}{3}} + 6x^{-7}$ -6. $= \dfrac{4}{3\sqrt[3]{x^2}} + \dfrac{6}{x^7}$ \ No newline at end of file +4. $f(x) = 4\sqrt[3]{x} = \dfrac{1}{x^6}$ +5. $= 4x^\frac{1}{3} - x^{-6}$ +6. $f'(x) = \dfrac{1}{3} * 4x^{-\frac{2}{3}} -(-6)(x^{-6-1})$ +7. $= 4x^{-2-\frac{2}{3}} + 6x^{-7}$ +8. $= \dfrac{4}{3\sqrt[3]{x^2}} + \dfrac{6}{x^7}$ \ No newline at end of file